Ghosts in the Adoption: Uncovering Parents' Attachment and Coping History. Issue 3 (July 2017) - Buckwalter, Karen Doyle; Reed, Debbie; Mercer, Danielle
Much has been written about the impact of trauma on adopted children, especially those adopted out of foster care or orphanage care. But what about trauma and/or attachment-related difficulties in the background of adoptive parents? The "state of mind with regard to attachment" (Main & Hesse, 2009) in parents makes a significant difference in parent–child relationships (van IJzendoorn, 1995), but this subject is rarely discussed compared to the trauma in adopted children. In this article, the Adult Attachment Interview (Main, Kaplan, & Cassidy 1985) is used to understand the history of adoptive parents and how it may impact the relationship with their adopted children. In addition to applying it during treatment with the family system, an unexpected benefit is the deepening of the therapeutic alliance with parents who are seeking help for their child as evidenced by clinician feedback.